Educating the Citizen of Academia Online? - Solberg, Mariann (International Review of Research in Open and Distributed Learning, 2011)
The Arctic is a vast, sparsely populated area. The demographic situation points to online distance education as a solution to support lifelong learning and to build competence in the region. An overall aim of all university education is what Hans Georg Gadamer calls Bildung, what we in Norwegian call dannelse and what Richard Rorty has called edification. A first problem to be addressed here is that in online distance learning some teachers find that is harder to support the development of the student’s voice. Being able to express oneself and to position oneself in a scientific community is vital for a well educated graduate. Another problem in online education has been the extensive use of writing as a means in the student’s learning process. Writing is vital to academic education, but in online courses there is in general a danger of overuse. At the University of Tromsø we have tested the web conference tool Elluminate Live. This is a real-time application, integrated in the University’s learning management system (LMS), Fronter. The application enables synchronous oral dialogue, simultaneous sharing of texts, and so forth. I present our main experience with the use of Elluminate Live and discuss the extent to which this application has turned out to be helpful in developing the quality of online courses.